Report of the Select Committee Raised to Inquire into the Amount of Dividends and Bonus Divided by the Banks of North Carolina, &c. (Document (North Carolina. General Assembly) ;, 1831)
1831 Select Committee report on the amount of dividends and bonus in the banks of North Carolina, specifically the State Bank, the Bank of Newbern, and the Bank of Cape Fear.